Front Cover: Direct Correlation between Adsorption Energetics and Nuclear Spin Relaxation in a Liquid‐saturated Catalyst Material (ChemPhysChem 19/2018). Issue 19 (21st September 2018) - Robinson, Neil; Robertson, Christopher; Gladden, Lynn F.; Jenkins, Stephen J.; D'Agostino, Carmine
Abstract : The Front Cover shows alcohol adsorption at a silica‐based catalyst support surface. The energetics of such interactions may be investigated non‐invasively through nuclear spin relaxation time measurements, as represented by the Bloch sphere. More information can be found in the Article by N. Robinson et al. on page 2472 in Issue 19, 2018 (DOI: 10.1002/cphc.201800513 ).